Search optimal control of induction heating modes for a moving workpiece. Issue 1 (7th January 2020) - Smolyanov, Ivan Alexandrovich; Tarasov, Fedor
Abstract : Purpose: This paper aims to create mathematical models and control algorithms allowing the authors to study and form effective modes of operation of multi-inductor system of electrical heating of moving hollow cylindrical blanks. Design/methodology/approach: The developed mathematical models were based on the finite-difference method, the control volume method and their combination. The reliability of the results obtained was verified by comparing the calculated results with the experimental ones. The temperature control system was synthesized using methods of the object management theory with distributed parameters. Findings: A set of mathematical instruments has been created that allow modelling the operation modes of installation for induction heating of moving hollow cylindrical blanks. Recommendations were given on the formation of an automatic control system that provides heating of a moving hollow cylindrical billet to the required temperature with simultaneous equalization of temperature along the length of the billet in case of highly uneven initial temperature along the length of the billet. Practical implications: Part of the paper will be used by the industrial plant for the purpose of heat treatment of iron alloys workpiece. Particularly, a control system will be basically formed based on the models. Originality/value: The scientific novelty of the paper is to create control algorithms and mathematical models for the induction heating system of tubular workpieces allowing to explore interrelated electromagnetic and thermal processes taking into account nonlinearities and design features of the system, as well as to form effective modes of its operation based on transfer functions and methods of the object management theory with distributed parameters.